A Combined Clinical and Serum Biomarker-Based Approach May Allow Early Differentiation Between Patients With Minor Stroke and Transient Ischemic Attack as Well as Mid-term Prognostication - Pelz, Johann Otto; Kubitz, Katharina; Kamprad-Lachmann, Manja; Harms, Kristian; Federbusch, Martin; Hobohm, Carsten; Michalski, Dominik (Frontiers in Neurology, 2021)
Background: Early differentiation between transient ischemic attack (TIA) and minor ischemic stroke (MIS) impacts on the patient’s individual diagnostic work-up and treatment. Furthermore, estimations regarding persisting impairments after MIS are essential to guide rehabilitation programs. This study evaluated a combined clinical- and serum biomarker-based approach for the differentiation between TIA and MIS as well as the mid-term prognostication of the functional outcome, which is applicable within the first 24 hours after symptom onset. Methods: Prospectively collected data were used for a retrospective analysis including the neurological deficit at admission (National Institutes of Health Stroke Scale, NIHSS) and the following serum biomarkers covering pathophysiological aspects of stroke: Coagulation (fibrinogen, antithrombin), inflammation (C reactive protein), neuronal damage in the cellular (neuron specific enolase (NSE)) and the extracellular compartment (matrixmetalloproteinase-9 (MMP-9), hyaluronic acid). Further, cerebral magnetic resonance imaging was performed at baseline and day 7, while functional outcome was evaluated with the modified Rankin Scale (mRS) after 3, 6, and 12 months. Results: Based on data from 96 patients (age 64±14 years), 23 TIA patients (NIHSS 0.6±1.1) were compared with 73 MIS patients (NIHSS 2.4±2.0). In a binary logistic regression analysis, the combination of NIHSS and serum biomarkers differentiated MIS from TIA with a sensitivity of 91.8% and a specificity of 60.9% (area under the curve (AUC) 0.84). In patients with NIHSS 0 at admission, this panel resulted in a still acceptable sensitivity of 81.3% (specificity 71.4%, AUC 0.69) for the differentiation between MIS (n=16) and TIA (n=14). By adding age, remarkable sensitivities of 98.4%, 100%, and 98.2% for the prediction of an excellent outcome (mRS 0 or 1) were achieved with respect to time points investigated within the one-year follow-up. However, the specificity was moderate and decreased over time (83.3%, 70%, 58.3%; AUC 0.96, 0.92, 0.91). Conclusion: This pilot study provides evidence that the NIHSS combined with selected serum biomarkers covering pathophysiological aspects of stroke may represent a useful tool to differentiate between MIS and TIA within 24 hours after symptom onset. Further, this approach may accurately predict the mid-term outcome in minor stroke patients, which might help to allocate rehabilitative resources.